2003
DOI: 10.1002/ana.3000
|View full text |Cite
|
Sign up to set email alerts
|

Outcome in psychogenic nonepileptic seizures: 1 to 10‐year follow‐up in 164 patients

Abstract: Our knowledge of longer term outcome in psychogenic nonepileptic seizures (PNESs) patients is limited; we know less still about factors predicting prognosis. This study was intended to describe outcome in a large cohort and to identify predictive clinical and psychological factors to generate new ideas for treatment. One hundred sixty-four adult patients with PNESs (66.7%) responded to outcome, personality, and psychosymptomatology questionnaires (Dimensional Assessment of Personality Pathology-Basic Questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
263
2
11

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 338 publications
(296 citation statements)
references
References 46 publications
20
263
2
11
Order By: Relevance
“…For example, the Goldstein et al trial employed measures assessing clinical outcome (seizure frequency diary), psychosocial outcome (work and social adjustment), psychopathology outcome (fear, depression), as well as several secondary outcome measures of health perceptions and locus of control [34]. Reuber et al [35] examined long-term NES outcomes from the standpoint of seizure outcome and government disability status and found that several clinical and psychological factors were associated with better prognosis. However, they pointed out that some variables are not conducive to intervention, such as history of better education and less violent seizures.…”
Section: General Issues Regarding Outcome Measurement In Nesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the Goldstein et al trial employed measures assessing clinical outcome (seizure frequency diary), psychosocial outcome (work and social adjustment), psychopathology outcome (fear, depression), as well as several secondary outcome measures of health perceptions and locus of control [34]. Reuber et al [35] examined long-term NES outcomes from the standpoint of seizure outcome and government disability status and found that several clinical and psychological factors were associated with better prognosis. However, they pointed out that some variables are not conducive to intervention, such as history of better education and less violent seizures.…”
Section: General Issues Regarding Outcome Measurement In Nesmentioning
confidence: 99%
“…Similarly, changing maladaptive personality characteristics may also prove difficult. Targeting personality characteristic change may also prove difficult, but they suggested that it may be possible to "concentrate on the identification and management of stressors or triggers in the (social) environment that interact with personality vulnerability" [35].…”
Section: General Issues Regarding Outcome Measurement In Nesmentioning
confidence: 99%
“…5 Patients with PNES experience long-term economic and social dependence, have frequent emergency department visits and hospital admissions, and incur high medical care costs. [6][7][8] The prognosis for the untreated illness is poor, with 71% of patients having ongoing psychogenic seizures and 56% of patients on disability at 1-to 10-year follow-up. 7 Psychotherapy has been shown to reduce psychogenic seizure frequency and improve quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] The prognosis for the untreated illness is poor, with 71% of patients having ongoing psychogenic seizures and 56% of patients on disability at 1-to 10-year follow-up. 7 Psychotherapy has been shown to reduce psychogenic seizure frequency and improve quality of life. The strongest evidence basis, including two randomized trials, demonstrates the efficacy of cognitive behavioral therapy.…”
Section: Introductionmentioning
confidence: 99%
“…NEPN'si olan hastaların tedavi sürecinin; tanıyı hastaya deklare etme sürecinde başladığı ve bu aşamada kullanılan etkin bir iletişimin hastanın tedavisine büyük katkı sağlayacağı bildirilmiştir. [22] Reuber ve ark.nın [23] çalışmalarında, 164 NEPN hastasının tanı sonrası 1-10 yıllık takiplerinde %70'inde nöbetlerin sürdüğü belirtilmiştir. Son yıllarda yapılan bir çalışmada ise NEPN'si olan 260 hastanın, tanı sonrası 6-12 ay süre ile takip edildiği ve sadece %38'inde nöbetlerin izlenmediği bildirilmiştir.…”
Section: Tablo 3 Grup 1 Ve Grup 2 Hastaların Takip Tanılarıunclassified